The Trump tax cut : your personal guide to the new tax law - Rosenberg, Eva (Humanix Books, 2019)
President Trump<U+2019>s new tax law is fully effective, and millions are finding out about the little-known “Trump Tax Loophole.” This guide explains the new loophole and how taxpayers like you can save billions in taxes. With this loophole you can slash your personal taxes by an additional 20%! That<U+2019>s if you qualify <U+2014> and many Americans do. This guide shows you how. The Trump Tax Cut is your guidebook to the biggest tax cut in history. In plain English, it reveals how you can benefit from the new law. You will find more than 200 deductions, write-offs and legal loopholes that will make your fortune real!